Discovery of cell active macrocyclic peptides with on-target inhibition of KRAS signaling. Issue 48 (30th November 2021) - Lim, Shuhui; Boyer, Nicolas; Boo, Nicole; Huang, Chunhui; Venkatachalam, Gireedhar; Angela Juang, Yu-Chi; Garrigou, Michael; Kaan, Hung Yi Kristal; Duggal, Ruchia; Peh, Khong Ming; Sadruddin, Ahmad; Gopal, Pooja; et al.
Abstract : Targeting undruggable intracellular proteins with peptides: novel on-target macrocyclic peptide inhibitors of KRAS with broad inhibition of proliferation of multiple KRAS-dependent cancer cell lines. Abstract : Macrocyclic peptides have the potential to address intracellular protein–protein interactions (PPIs) of high value therapeutic targets that have proven largely intractable to small molecules. Here, we report broadly applicable lessons for applying this modality to intracellular targets and specifically for advancing chemical matter to address KRAS, a protein that represents the most common oncogene in human lung, colorectal and pancreatic cancers yet is one of the most challenging targets in human disease. Specifically, we focused on KRpep-2d, an arginine-rich KRAS-binding peptide with a disulfide-mediated macrocyclic linkage and a protease-sensitive backbone. These latter redox and proteolytic labilities obviated cellular activity. Extensive structure–activity relationship studies involving macrocyclic linker replacement, stereochemical inversion, and backbone α-methylation, gave a peptide with on-target cellular activity. However, we uncovered an important generic insight – the arginine-dependent cell entry mechanism limited its therapeutic potential. In particular, we observed a strong correlation between net positive charge and histamine release in an ex vivo assay, thus making this series unsuitable for advancement due to the potentially fatal consequences of mast cell degranulation. This observation should signal to researchers that cationic-mediated cell entry – an approach that has yet to succeed in the clinic despite a long history of attempts – carries significant therapy-limiting safety liabilities. Nonetheless, the cell-active molecules identified here validate a unique inhibitory epitope on KRAS and thus provide valuable molecular templates for the development of therapeutics that are desperately needed to address KRAS-driven cancers – some of the most treatment-resistant human malignancies.